A selective "turn-on" sensor for recognizing In3+ and Zn2+ in respective systems based on imidazo[2, 1-b]thiazole. Issue 2 (5th February 2020) - Xu, Yuankang; Zhao, Songfang; Zhang, Yanxia; Wang, Hanyu; Yang, Xiaofeng; Pei, Meishan; Zhang, Guangyou
Abstract : An imidazo[2, 1- b ]thiazole-based compound (X ) was designed and synthesized as an "off–on–off" sensor for the multiple recognition of In 3+ and Zn 2+ in different systems. Abstract : A new simple and easily synthesized multitarget sensor, ( E )- N ′-(4-(diethylamino)-2-hydroxybenzylidene)imidazo[2, 1- b ]thiazole-6-carbohydrazide (X ), was designed and synthesized using imidazo[2, 1- b ]thiazole-6-carboxylic acid and 4-(diethylamino)-2-hydroxybenzaldehyde. X could be used as a sensor to detect In 3+ in DMF–H2 O buffer solution and detect Zn 2+ in EtOH–H2 O buffer solution through fluorescence enhancement with detection limits of 1.02 × 10 −9 M and 5.5 × 10 −9 M, respectively. X exhibited an efficient "off–on–off" fluorescence behavior by cyclic addition of metal ions (In 3+ and Zn 2+ ) and EDTA. The stoichiometry between X and metal ions (In 3+ and Zn 2+ ) was 1 : 1. The binding mode and sensing mechanism of X with metal ions (In 3+ and Zn 2+ ) was verified by theoretical calculations using Gaussian 09 based on B3LYP/6-31G(d) and B3LYP/LANL2DZ basis, respectively. Moreover, X could be applied as a potential sensor for the quantitative detection of In 3+ and Zn 2+ with a satisfactory recovery and relative standard deviation (RSD) in real water samples.